Early and late allergic reactions limited to adalimumab injection sites in a patient with severe plaque psoriasis - Obtułowicz, Aleksander; Barouka, Daryna; Kapusta, Dominika; Kapczyński, Norbert; Lato, Marta; Jaworek, Andrzej; Obtułowicz, Bartosz; Wojas-Pelc, Anna (Alergologia Polska - Polish Journal of Allergology, 2025)
Tumor necrosis factor-α (TNF-α) inhibitors, such as adalimumab, are widely used for the treatment of various inflammatory diseases, including psoriasis. Injection site reactions (ISRs) are common side effects, typically mild and self-limiting. Nevertheless, in some cases, ISRs may persist or evolve into more severe hypersensitivity reactions, requiring discontinuation or a change of the therapy. We present the case of a 40-year-old woman with plaque psoriasis who developed progressive ISRs and recall reactions during adalimumab therapy. Allergological diagnostics confirmed a delayed-type hypersensitivity reaction. Transitioning to an IL-12/IL-23 inhibitor resulted in clinical improvement, highlighting the importance of allergological testing and alternative biologic therapies.